The role of dermoscopy in non-pigmented skin disorders - Fathan, Hafiza; Indriatmi, Wresti; Rihatmadja, Rahadi; Krisanti, Inge Ade (UI Scholars Hub, 2016)
The use of dermoscopy in non-pigmented skin disorders includes dermoscopy as a diagnostic tool for non- pigmented skin tumors, inflammatory diseases (inflammoscopy) and/or infectious disease (entomodermoscopy), lesions on nail fold and as a tool to monitor skin reaction as a response to treatment and/or side effect. The diagnosis becomes easier, faster and less expensive with dermoscopy without the need for invasive procedures. Knowledge on vascular pattern and its architectural arrangement; which is coupled with additional dermoscopic features, can aid clinicians to the diagnosis. Dermatoscopy can also predict, monitor and evaluate therapeutical response and/or side effect of skin disorders. Nonetheless, dermoscopy has its limitations. Many of various non-pigmented disorders have more specific clinical features than dermoscopic ones, for clinicians to rely on to establish a diagnosis.